2016
DOI: 10.1016/j.ribaf.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Tick test accuracy in foreign exchange ECN markets

Abstract: Recent changes in quoting activity have increased the allure of the Tick test because the quote rule and its variants require matching asynchronous trade and quote records. We find Tick test accuracy of forex USD/Euro trades in 2005/6 is 66%. The accuracy falls to 60% for zero tick trades (half the sample), with a disturbing asymmetry between buyer (61%) and seller (70%) initiated trades. We also observe extreme asymmetry for quote changes, where buyer accuracy is 96% (29%) for up (down) quote changes, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Aktas and Kryzanowski (2014) examined the trade classification accuracy of different classification algorithms using the data of component firms of the BIST-30 index and found that the classification success rate of the tick rule ranged from 84.86% to 92.15% in different subsamples. In addition, Omrane and Welch (2016) found that the classification success rate of the tick rule for 1.2 million trades on the foreign exchange electronic communication network market was about 68%. To the best of the authors' knowledge, none of the previous research has focused on the accuracy of trade classification algorithms for the cryptocurrency markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aktas and Kryzanowski (2014) examined the trade classification accuracy of different classification algorithms using the data of component firms of the BIST-30 index and found that the classification success rate of the tick rule ranged from 84.86% to 92.15% in different subsamples. In addition, Omrane and Welch (2016) found that the classification success rate of the tick rule for 1.2 million trades on the foreign exchange electronic communication network market was about 68%. To the best of the authors' knowledge, none of the previous research has focused on the accuracy of trade classification algorithms for the cryptocurrency markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More recently, Chakrabarty et al (2012) assess the performance of the Lee-Ready procedure by comparing its results to a sign provided by the exchange (i.e. not using quotes data) and find on 2005 data a misclassification by the Lee-Ready procedure of the order of magnitude of 20 to 30% (similar to Omrane & Welch (2016) on 2005 data as well). Please note these few references have been selected just as an illustration with various data (from 1996 to 2005), references in each of them should be checked for further details.…”
Section: Number Of Reported Transactionsmentioning
confidence: 99%